2021
DOI: 10.1177/2473974x211059429
|View full text |Cite
|
Sign up to set email alerts
|

Times to Diagnosis, Staging, and Treatment of Head and Neck Cancer Before and During COVID‐19

Abstract: Objective The coronavirus disease 2019 (COVID-19) pandemic has reduced the demand for, and supply of, head and neck cancer services. This study compares the times to diagnosis, staging, and treatment of head and neck cancers before and during the COVID-19 pandemic. Study Design Retrospective cohort study. Setting Tertiary academic medical center in New York City (NYC). Methods The times to diagnosis, staging, and treatment of head and neck cancer for patients presenting to the clinics of 4 head and neck oncolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
(35 reference statements)
2
10
1
Order By: Relevance
“…In the United States, only a small retrospective cohort study has been published to address time to diagnosis and treatment of head and neck cancer. 14 In this study by Yao et al, time from suspicion of cancer to diagnosis and time from diagnosis to treatment were similar between COVID and pre‐COVID cohorts. Our study corroborates these findings, indicating that concerns regarding potential delays in cancer care during the COVID era have generally not materialized.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In the United States, only a small retrospective cohort study has been published to address time to diagnosis and treatment of head and neck cancer. 14 In this study by Yao et al, time from suspicion of cancer to diagnosis and time from diagnosis to treatment were similar between COVID and pre‐COVID cohorts. Our study corroborates these findings, indicating that concerns regarding potential delays in cancer care during the COVID era have generally not materialized.…”
Section: Discussionmentioning
confidence: 48%
“…They also found that time from diagnosis to treatment was shorter in the COVID pandemic when compared with pre‐COVID years. In the United States, only a small retrospective cohort study has been published to address time to diagnosis and treatment of head and neck cancer 14 . In this study by Yao et al, time from suspicion of cancer to diagnosis and time from diagnosis to treatment were similar between COVID and pre‐COVID cohorts.…”
Section: Discussionmentioning
confidence: 73%
“…However, an extension of the time to diagnosis was not significant in two studies 8 , 9 , while Yao et al reported a longer time to diagnosis (p = 0.02) but not to staging 11 . Four studies showed a significant increase in tumour size (p = 0.042) 8 and in T stage 9 , 10 , 12 at presentation in the COVID group.…”
Section: Resultsmentioning
confidence: 80%
“…In 2021, Teveteglu et al reported a significantly higher (p = 0.02) mean time from the beginning of the first symptom to hospital admission in patients treated in 2020 compared to those treated in 2019 10 . Similarly, Yao et al found that patients in the COVID-19 group had a significantly longer time to diagnosis than the pre-COVID-19 group after adjustment for age and cancer diagnosis (p = 0.02; HR, 0.54; 95% CI, 0.32-0.92) 11 .…”
Section: Discussionmentioning
confidence: 89%
“…It must be considered, however, that, although there was no difference in the time between the diagnosis and the start of treatment, the mean time interval veri ed in the present study was high, mainly considering the results of other studies, which demonstrated a mean time of 20 to 28 days between the rst patient visit and initiation of treatment during the COVID-19 period. [10,22] The impact of delayed diagnosis and initiation of HNSCC treatment on patient survival has been studied. [23] Previous studies that investigated the association between the time interval between diagnosis and treatment initiation and the overall survival of patients with HNSCC found that the time elapsed between diagnosis and initiation of treatment independently affects patient survival, increasing the 5-year mortality risk.…”
Section: Resultsmentioning
confidence: 99%